How far you have come : musings on beauty and courage - Nichols, Morgan Harper, 1990- (Zondervan, 2021)
"How Far You Have Come is an exquisite collection of poetry and essays from bestselling artist and writer Morgan Harper Nichols. In the midst of the hurt and the mundane, the questions and the not yets, we can forget just how far we have come. Morgan weaves together personal reflections with her signature poems to share her journey to reclaim moments of brokenness, division, and pain and re-envision them as experiences of reconciliation, unity, and hope. The stories in How Far You Have Come are organized around a familiar path Morgan has traveled all her life, along the southern border of the United States. As Morgan reflects on the moments that shaped her, she invites us to: Awaken our hearts and recognize how our own histories have made us who we are today. Have a deeper understanding of pressing on and pressing in, of transformation and surrender, of meaning in the losses and wild anticipation for the splendor ahead . Reclaim moments of brokenness, division, and pain and re-envision them as experiences of reconciliation, unity, and hope. Become who we are in the moment you hold right now."--Publisher's website.